SIK1 Regulates CRTC2-Mediated Gluconeogenesis Signaling Pathway in Human and Mouse Liver Cells - Wang, Chang; Song, Daofei; Fu, Jiahui; Wen, Xiuying (Frontiers in Endocrinology, 2020)
The regulation of hepatic gluconeogenesis is of great significance to improve insulin resistance and benefit diabetes therapy. cAMP-Regulated Transcriptional Co-activator 2 (CRTC2) plays a key role in regulating hepatic gluconeogenesis through controlling the expression of gluconeogenic rate-limiting enzymes such as glucose-6-phosphatase (G6Pase) and phosphoenolpyruvate carboxykinase (PEPCK). Recently, salt-inducible kinase 1 (SIK1) has been identified to play an important role in glucose metabolism disorders, but whether and how SIK1 regulates the CTRC2 signaling in liver cells under high glucose conditions has rarely been intensively elucidated. Here, we show that high glucose stimulation resulted in time-dependent down-regulated expression of SIK1, phosphorylated SIK1 at T182 site, and phosphorylated CRTC2 at S171 site, as well as upregulated expression of total CRTC2 and its downstream targets G6Pase and PEPCK in the human liver cell line HepG2. The nuclear expression levels of SIK1 and CRTC2 were time-dependently upregulated upon high glucose challenge, which was accompanied by enhanced cytoplasm-to-nucleus translocation of SIK1. Manipulation of SIK1 activity using plasmid-mediated SIK1 over-expression and the use of the SIKs inhibitor HG-9-91-01 confirmed that SIK1 regulated the CRTC2 signaling pathway in HepG2 cells. Furthermore, in mouse primary hepatocytes, high glucose exposure down-regulated SIK1 expression and promoted SIK1 nuclear accumulation. While HG-9-91-01 treatment suppressed SIK1 expression and released the inhibitory effects of SIK1 on the expressions of key molecules involved in the CRTC2 signaling pathway, additional ectopic expression of SIK1 using adenovirus infection reversed the impacts of HG-9-91-01 on the expressions of these molecules in mouse hepatocytes. Therefore, SIK1 regulates CRTC2-mediated gluconeogenesis signaling pathway under both physiological and high glucose-induced pathological conditions. The modulation of the SIK1-CRTC2 signaling axis could provide an attractive means for treating diabetes.